Neuroangiostrongyliasis due to Angiostrongylus cantonensis in gang‐gang cockatoos (Callocephalon fimbriatum). Issue 11 (28th October 2013) - Reece, RL; Perry, RA; Spratt, DM
<x xml:space="preserve">Abstract</x> Case report Four gang‐gang cockatoos from an aviary in Sydney displayed severe neurological signs. Three were necropsied and histopathology of the brains and spinal cords revealed migrating nematodes, which were identified as Angiostrongylus cantonensis. The migrating larval nematodes created tracts of malacia in the brain, but elicited little inflammatory cell infiltration. However, adult nematodes that had emerged onto the meningeal surface of the spinal cord evoked a marked non‐suppurative reaction. Detailed histological examination of other tissues revealed larvae embedded in arterioles in the gastrointestinal serosa, lung and heart, which were associated with a significant granulomatous response. The latter lesions were consistent with our understanding of the pathogenesis of infection with this parasite, but have not been previously described, probably as a result of limited sampling. Conclusions Angiostrongylus cantonensis is still present in the Sydney area and can cause significant disease in exposed animals, including birds. It also highlights potential human health problems.